2009
DOI: 10.1039/b821406a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic communication in oligonuclear ferrocene complexes with anionic four-coordinate boron bridges

Abstract: The di- and trinuclear ferrocene species Li[Fc-BPh(2)-Fc] (Li[]) and Li(2)[Fc-BPh(2)-fc-BPh(2)-Fc] (Li(2)[]) have been investigated with regard to their electrochemical properties and the degree of intervalence charge-transfer after partial oxidation. Li[] shows two distinct one-electron redox waves for its chemically equivalent ferrocenyl substituents in the cyclic voltammogram (E(1/2) = -0.38 V, -0.64 V; vs. FcH/FcH(+)). The corresponding values of Li(2)[] are E(1/2) = -0.45 V (two-electron process) and -1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
(122 reference statements)
4
24
0
Order By: Relevance
“…We therefore conclude that the attachment of anionic borate substituents may help to stabilize a broader variety of Li + -π interactions. This conclusion is supported by the solid-state structures of IV, [30] V, [31] and VI, [32] which all feature Li + -benzene π coordination ( Figure 1). In IV-VI, the desired structural motif is still enforced by a chelating side arm.…”
Section: Introductionsupporting
confidence: 54%
“…We therefore conclude that the attachment of anionic borate substituents may help to stabilize a broader variety of Li + -π interactions. This conclusion is supported by the solid-state structures of IV, [30] V, [31] and VI, [32] which all feature Li + -benzene π coordination ( Figure 1). In IV-VI, the desired structural motif is still enforced by a chelating side arm.…”
Section: Introductionsupporting
confidence: 54%
“…Oligoferrocenes have attracted enormous interest in the past years because of their applicability in molecular electronics and multi‐redox catalysis 1–4. Linear processablepoly(ferrocenylenes) were pioneered by Manners, who obtained these compounds by the ring‐opening polymerization of ER 2 ‐bridged [1]ferrocenophanes (E = C, Si, Ge, Sn), and Wagner, who used BR n linkers 59…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to the perpendicular orientation of the p orbital at boron towards the conjugated spacer-system, thus insulating it from the ferrocene moieties. [36] It should be added that the B=N double bonds (vide infra) could also reduce the degree of electrochemical communication by lowering the Lewis acidity of the boron centers. [37] Subsequent experiments have shown that the diastereomers 4 and 5 can easily be interconverted.…”
mentioning
confidence: 99%